Evidence of hybrid speciation in the North American primroses Primula suffrutescens, P. parryi, P. rusbyi and P. angustifolia (Primulaceae) - CIANCHI, Maria Rossella; BULLINI, Luciano; P. Arduino; M. C. Mosco (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2015)
The genetic structure of tetraploid (4x = 44) North American species of Primula subgenus Auriculastrum: P. suffrutescens,P. parryi, P. rusbyi, and P. angustifolia was analyzed at seven enzyme loci and compared with that of the related diploidP. cuneifolia and P. nipponica. The studied tetraploid species showed fixed or almost fixed heterozygosity at various loci,indicating a hybrid origin. About half of their alleles were shared with Cuneifolia taxa sampled, suggesting that they arose from crosses involving a maternal Cuneifolia-like ancestor. A preliminary survey of their possible paternal species, as inferred from their genotypes, was carried out among different Primula groups. Several paternal alleles expected were observed in subgenus Aleuritia, particularly among taxa of sect. Crystallophlomis (e.g., P. chionantha, P. minor, and P. nivalis xanthobasis). However, none of these taxa proved to be a suitable paternal species. Hybridization events that originated P. suffrutescens, P. parryi, P. rusbyi, and P. angustifolia presumably occurred during Pleistocene secondary contacts in Beringia and involved a maternalCuneifolia-like ancestor and at least two paternal species, for sect. Suffrutescens and Parryi, respectively. Further studies,involving a genetic survey of Aleuritia taxa from Siberia will be needed to detect such paternal species, if not extinct.